VULNERABILITY OF UKRAINIAN AIRSPACE TO ATTACKS BY THE RUSSIAN FEDERATION AS A RESULT OF UKRAINE’S MISSILE AND NUCLEAR DISARMAMENT IN THE 1990S (IMPACTS OF THE BUDAPEST MEMORANDUM) - Belkin, Leonid; Іurynets Juliya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The aim of the article is a comprehensive historical and legal analysis of the missile and nuclear disarmament of Ukraine in the 1990s and its impact on the vulnerability of Ukrainian airspace to attacks by the russian federation. Research methods: documentary and legal analysis and generalization of historical, legal, and political information. Results: the history of the missile and nuclear disarmament of Ukraine in the 1990s, the legal basis, and the consequences are studied. It is emphasized that such disarmament of Ukraine became possible «thanks» to the «guarantees» of national security and territorial integrity of Ukraine, provided to Ukraine under the Budapest Memorandum of 1994. These guarantees served as the basis not only for Ukraine’s refusal of nuclear status, but also for its refusal of the missile shield. However, the voluntary abandonment of missiles and strategic aviation put Ukraine at an extremely disadvantageous position in the war against the Russian Federation, as it led to a disparity in capabilities in terms of the difference in the ultimate reach of weapons of mass destruction. This is the result of the unilateral disarmament of Ukraine. Discussion: historically, the fact of the treacherous policy of the United States towards Ukraine should be recorded, the stages of which are: pressure on Ukraine for its missile and nuclear disarmament; transfer of the seized weapons to the obvious enemy of Ukraine – russia; imposition of «assurances» instead of «guarantees» during the preparation of the Budapest Memorandum, which later allowed the «guarantors» to legitimately evade the implementation of the Budapest Memorandum, «playing with words»; failure by the United States to comply with the agreements (Charters) on strategic partnership; insufficient military assistance, moreover, limited by all sorts of conditions, in the confrontation with the Russian Federation, which (the confrontation) could have been much more effective if Ukraine had not been deprived of its nuclear missile potential; criminal betrayal by the United States at the beginning of 2025, which consisted in a complete refusal to supply Ukraine with weapons and intelligence data, as well as in the non-recognition of the Russian Federation as an aggressor. After the beginning of 2025, the blood of Ukrainians and the destruction of the country are on the hands and conscience of the US leadership.